SARC006: Phase II Trial of Chemotherapy in Sporadic and Neurofibromatosis Type 1 Associated Chemotherapy-Naive Malignant Peripheral Nerve Sheath Tumors - Higham, Christine S. (Sarcoma, 2017)
BACKGROUND: Worse chemotherapy response for neurofibromatosis type 1- (NF1-) associated compared to sporadic malignant peripheral nerve sheath tumors (MPNST) has been reported. METHODS: We evaluated the objective response (OR) rate of patients with AJCC Stage III/IV chemotherapy-naive NF1 MPNST versus sporadic MPNST after 4 cycles of neoadjuvant chemotherapy, 2 cycles of ifosfamide/doxorubicin, and 2 cycles of ifosfamide/etoposide. A Simon optimal two-stage design was used (target response rate 40%). RESULTS: 34 NF1 (median age 33 years) and 14 sporadic (median age 40 years) MPNST patients enrolled. Five of 28 (17.9%) evaluable NF1 MPNST patients had a partial response (PR), as did 4 of 9 (44.4%) patients with sporadic MPNST. Stable disease (SD) was achieved in 22 NF1 and 4 sporadic MPNST patients. In both strata, results in the initial stages met criteria for expansion of enrollment. Only 1 additional PR was observed in the expanded NF1 stratum. Enrollment was slower than expected and the trial closed before full accrual. CONCLUSIONS: This trial was not powered to detect differences in response rates between NF1 and sporadic MPNST. While the OR rate was lower in NF1 compared to sporadic MPNST, qualitative responses were similar, and disease stabilization was achieved in most patients.